2021
DOI: 10.1002/aenm.202003457
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Quantum Dot Solar Cells: A Matter of (Life)Time

Abstract: stable QDSCs in the past years, and these will be discussed in the following sections both from materials science and device engineering perspectives. Several principal QD materials will be covered separately: lead chalcogenide QDs, lead halide perovskite QDs, and lead-free QDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 217 publications
(394 reference statements)
1
61
0
3
Order By: Relevance
“…[4] By virtue of their excellent optoelectronic properties, QDs have been highlighted in the fields of in vitro diagnostics, solar cells, single photon sources, and light-emitting diodes. [5][6][7][8][9][10][11][12] In particular, tremendous improvements in QDs synthesis methods and device engineering have pushed the performance of QDs light-emitting diodes (QLEDs) close to state-of-the-art organic light-emitting devices (OLEDs). [13][14][15][16] However, despite these merits of QDs, there are still some limitations that need to be overcome, such as the fluctuation of PL intensity of single QD, the photochemical stability of QDs, and the device stability and efficiency rolloff of QLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…[4] By virtue of their excellent optoelectronic properties, QDs have been highlighted in the fields of in vitro diagnostics, solar cells, single photon sources, and light-emitting diodes. [5][6][7][8][9][10][11][12] In particular, tremendous improvements in QDs synthesis methods and device engineering have pushed the performance of QDs light-emitting diodes (QLEDs) close to state-of-the-art organic light-emitting devices (OLEDs). [13][14][15][16] However, despite these merits of QDs, there are still some limitations that need to be overcome, such as the fluctuation of PL intensity of single QD, the photochemical stability of QDs, and the device stability and efficiency rolloff of QLEDs.…”
Section: Introductionmentioning
confidence: 99%
“…The excess-oxygen-related deep-level emissions were quenched completely, while the near band-edge emissions were greatly enhanced when H atoms were incorporated into ZnO NWs. These H atoms are most likely to exist in the form of shallow donors and may be removed after annealing at 400 [ 108 , 109 , 110 ]. Concerning the desorption of hydroxyl groups, Shi et al [ 108 ] confirmed that annealing at 150 results in the removal of OH groups, but it may also introduce other hydrogen-related impurities.…”
Section: Optimization Strategies Of Ibhj Qdscs Based On Zno Nwsmentioning
confidence: 99%
“…The need to develop complementary materials beyond Pb-QDs has also led to the development of luminescent solar concentrators (LSCs) featuring copper-doped InP/ZnSe QDs (Eren et al, 2021) and CdSe QDs (Albaladejo-Siguan et al, 2021). Similar to the DSSCs, the LSCs are cost-effective and simple solar energy harvesting devices.…”
Section: Pb-free Halide Perovskite Andmentioning
confidence: 99%
“…The observations made by Ravishankar et al (2020) were corroborated by Eren et al (2021), who synthesized copper-doped InP/ZnSe quantum dots for luminescent solar concentrators with an extremely lower power conversion efficiency of 3.4% and external quantum efficiency levels (EQE) of 5.9% (Eren et al, 2021). The PCEs of the materials was significantly low relative to Semitransparent (ST) organic solar cells with a PCE of 17%, Cu 2 O films (PCE-10%) (Ifeanyi et al, 2021), semitransparent polymer solar cells (PCE-7.7%) (Shi et al, 2019), Pb-halide perovskite (PCE-25.5%) (Albaladejo-Siguan et al, 2021). The low PCE offsets the unique benefits associated with the LSCs.…”
Section: Organic Pvmentioning
confidence: 99%
See 1 more Smart Citation